2019
DOI: 10.1016/s2352-4642(19)30024-0
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of CMV, HTLV-1, and HIV through breastmilk

Abstract: Breastfeeding is a critical child survival intervention. The potential for transmission of some viral infections from mother-to-child, however, presents the dilemma of how best to interpret the benefits and risks of breastfeeding in different settings. Here, we compare the transmission dynamics, risk factors and outcomes of infection with three chronic viruses transmitted through breast milk: cytomegalovirus (CMV), human T-cell lymphotropic virus type 1 (HTLV-1), and human immunodeficiency virus (HIV). We prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 96 publications
0
36
1
2
Order By: Relevance
“…The mechanism of postnatal HCMV-reactivation in the mammary gland without viral systemic infection (DNAemia) is still unknown. Virus-shedding into breast milk of immunocompetent healthy breastfeeding mothers occurs in nearly every seropositive mother at any time point during lactation, but usually ends 2-3 months after birth [3,4]. Transmission via breastfeeding can lead to severe symptomatic HCMV-infection in preterm infants, with increased risk with birth weight below 1500 g or less than 32 weeks of gestational age [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of postnatal HCMV-reactivation in the mammary gland without viral systemic infection (DNAemia) is still unknown. Virus-shedding into breast milk of immunocompetent healthy breastfeeding mothers occurs in nearly every seropositive mother at any time point during lactation, but usually ends 2-3 months after birth [3,4]. Transmission via breastfeeding can lead to severe symptomatic HCMV-infection in preterm infants, with increased risk with birth weight below 1500 g or less than 32 weeks of gestational age [2].…”
Section: Introductionmentioning
confidence: 99%
“…Colostrum (up to one week postpartum (pp)) is considered especially important for newborns. Colostrum is followed by transient milk (2)(3)(4) weeks pp) and mature milk (more than 4 weeks pp). The World Health Organization (WHO) recommends exclusive breastfeeding for the first six months of life [10].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the public health importance of HHV-6 and CMV infections and the interest in preventing HHV-6-related diseases, understanding the determinants of transmission is of great interest. CMV transmission to infants has been shown to occur most commonly via breast milk, though saliva and urine are other routes of infection during early childhood [9,[20][21][22][23]. HHV-6 is likely transmitted through saliva, based on the frequency of the viral detection of the virus in the saliva of infected individuals [3]; in contrast, HHV-6 infection is not associated with breastfeeding and is rarely found in breast milk [9,24].…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors for HTLV-1 MTCT other than longterm breastfeeding are known, including high mother HTLV-1 antibody titers and PVL (Ureta-Vidal et al, 1999;Hisada et al, 2002;Paiva et al, 2018). Paiva et al (2018) reported that breastfeeding ≥12 months, higher maternal PVL (≥ 100 copies/10 4 PBMC) and ≥ 2 previous HTLV-1-infected children were independently associated with MTCT in a multiple logistic regression. Hisada et al (2002) suggests that mothers who have a high PVL (≥ 3%) should be encouraged not to breast-feed, while a risk of the transmission in low PVL less than 0.1% was negligible.…”
Section: Elimination or Reduction Of The Benefits Obtained By Breastfmentioning
confidence: 99%
“…The potential for viral transmission from mother to child presents a dilemma on how best to interpret the benefits and risks of breastfeeding in different settings (Prendergast et al, 2019). Meta-analysis has shown that feeding with the mother's own milk or banked human milk can reduce the risk of necrotizing enterocolitis and/or severe infections, especially for very lowbirth-weight infants (<1,500 g birth weight) or very preterm infants (<32 weeks of gestation) (Corpeleijn et al, 2016;Miller et al, 2018).…”
Section: Very Preterm And/or Very Low-birth-weight Infants Born To Camentioning
confidence: 99%